CONSIDERATIONS REGARDING THE GUARANTEEING OF HUMAN RIGHTS IN ROMANIA - ELENA PARASCHIV (Challenges of the Knowledge Society)
In our country existed and exists still a constant concern to respect and guarantee human rights and fundamental freedoms, especially after 1989, when Romania became a member or acceding to international or regional treaties and conventions enshrining such rights. Taking into consideration the importance of respecting human rights, we consider that is necessary to research how they are secured in Romania, because only when these guarantees are known by their beneficiaries and those involved in their protection, actions which affect these values of humanity can be avoided. In human rights, rules of international law have priority over those entered in the domestic law if they contain provisions which may be interpreted differently on the same matter, unless the Constitution or national laws contain more favourable provisions.